Estimation, Calculation, And Mapping Of The Greenhouse Gas Residential And Transportation Sector In Gunung Anyar District - Hana Nisrina Alifiyah; Muhammad Mirwan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to estimate and map greenhouse gas (GHG) emissions from the transportation and residential sectors in Gunung Anyar District, Surabaya City. The methodology used follows the Intergovernmental Panel on Climate Change (IPCC) Guidelines 2006, employing a Tier 1 approach based on activity data and default emission factors. Emissions estimates for the residential sector were calculated from household electricity and LPG consumption, while those for the transportation sector were calculated from motor vehicle fuel consumption. Research data were obtained through questionnaire distribution and secondary data collection from relevant agencies. The estimated emissions were analysed and projected in LEAP and spatially mapped in ArcGIS to determine the distribution in the study area. This study is expected to provide policymakers and stakeholders with a foundation for effective emission-control and climate change mitigation strategies in Gunung Anyar Subdistrict. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action